2013
DOI: 10.1155/2013/186505
|View full text |Cite
|
Sign up to set email alerts
|

Antimelanoma and Antityrosinase from Alpinia galangal Constituents

Abstract: Two compounds, 1,7-bis(4-hydroxyphenyl)-1,4,6-heptatrien-3-one (BHPHTO) and bisdemethoxycurcumin (BDMC) they have been isolated from the rhizomes of Alpinia galangal, and the structures of both pure constituents were determined using spectroscopic analyses. The study examined the bioeffectivenesses of the two compounds on the human melanoma A2058 and showed that significantly inhibited the proliferation of melanoma cells in the cell viability assay. This research was also taken on the tests to B16-F10 cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…However, only a few natural and synthetic depigments are used as therapeutic agents because of safety concerns and low whitening bioactivity. 4,5 Melanin synthesis in melanocytes, in which tyrosinase plays a critical role, is mediated by several enzymes. 6 The pathway of melanin biosynthesis can be divided into two main parts: the production of eumelanin (eumelanogenesis) and the production of pheomelanin (pheomelanogenesis) ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, only a few natural and synthetic depigments are used as therapeutic agents because of safety concerns and low whitening bioactivity. 4,5 Melanin synthesis in melanocytes, in which tyrosinase plays a critical role, is mediated by several enzymes. 6 The pathway of melanin biosynthesis can be divided into two main parts: the production of eumelanin (eumelanogenesis) and the production of pheomelanin (pheomelanogenesis) ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…[19][20][21] In our presented study, the concentrations of curcumin lower than 2 μM might be no cytotoxic effect on Detroit 551 cells (Fig. 1(B)).…”
Section: Targetmentioning
confidence: 46%
“…In a study, Lo et al . reported that two compounds namely, 1,7‐bis(4‐hydroxyphenyl)−1,4,6‐heptatrien‐3‐one (BHPHTO) and bisdemethoxycurcumin (BDMC) can inhibit the proliferation of melanoma cells . Moreover, Faião‐Flores et al .…”
Section: Curcumin Analogs As Powerful Tools In Melanoma Therapymentioning
confidence: 99%
“…In a study, Lo et al reported that two compounds namely, 1,7-bis(4-hydroxyphenyl)21,4,6-heptatrien-3-one (BHPHTO) and bisdemethoxycurcumin (BDMC) can inhibit the proliferation of melanoma cells. 112 Moreover, Faião-Flores et al revealed that curcumin analogue DM-1, alone or in combination with dacarbazine (DTIC), shows anti-tumor effects as it inhibited melanoma progression in a melanoma mouse model. 113 In addition, no toxicological changes were observed in organs such as the spleen, kidneys, liver and lungs after the administration of DM-1, either alone or in combination with DTIC.…”
Section: Curcumin Analogs As Powerful Tools In Melanoma Therapymentioning
confidence: 99%